Effect of pulsed vacuum and laser microperforations on the potential acceleration of chicken meat marination. (22nd December 2020) - Ramírez, Natalia; Vega‐Castro, Oscar; Simpson, Ricardo; Ramirez, Cristian; Nuñez, Helena
Abstract: Chicken meat marination has become a fundamental process in the poultry industry since it provides a product with better sensory attributes. The objective of this study was to examine the effect of CO2 laser microperforation coupled with vacuum impregnation treatment on the marination processing time of chicken breasts and to mathematically analyze the marinade diffusion process using Fick's second law and an anomalous diffusion model. Cylindrical cuts of unmarinated chicken meat were CO2 ‐laser microperforated with pores of 228 μm and marinated under vacuum pressure (15 kPa) with NaCl (3% wt/wt) and sodium tripolyphosphate (1% wt/wt) during 60 hr at 6 ° C. The chicken:brine ratio was 1:11 wt/wt. Mass gain, moisture content, and salt concentration were determined over time; furthermore, effective diffusion coefficient ( D eff ) was obtained using Fick's second law and anomalous diffusion models. Marinade diffusion into chicken cuts was favored by microperforation combined with vacuum pulses, reduction processing time in 34%. The D eff ranged between 1.46 × 10 −10 and 2.08 × 10 −10 m 2 /s for Fick's second law and between 2.27 × 10 −10 and 4.23 × 10 −10 m 2 /s α for anomalous diffusion model, with α −values close to 1. In conclusion, the results showed no significant difference between the models, which was attributed to the homogeneity of the chicken tissue. Practical Applications: Chicken meat marination has become a fundamental process in the poultry industry since it provides a product with better sensory attributes and shelf life than unmarinated chicken meat. Nevertheless, marination is a process that requires a long processing time to obtain a specified salt content in the meat. In this sense, laser microperforation of the meat is a treatment that when coupled with vacuum impregnation, can accelerate the marinating process of poultry meat. When simultaneously applying both technologies, the processing time was reduced by 6 hr compared with the control (almost 34%), which will allow a significant increase in plant productivity.